Do Working Capital Efficiency and Capital Structure Shape Financial Distress? The Moderating Role of Firm Size in Food and Beverage Firms Listed on the Indonesia Stock Exchange - Aditya Rahmadani; Solikah Nurwati; Putri Salasyah Riadin Nengsih; Novia Safitri (JURNAL ECONOMINA, 2026)
This study examines Cash Conversion Cycle (CCC) and Debt to Equity Ratio (DER) as determinants of financial distress, with firm size tested as a moderating variable, among Food and Beverage companies on the IDX during 2021–2025. Financial distress is operationalized through the Altman Emerging Market Score (EMS), estimated via a Fixed Effect Model with clustered standard errors using panel data from 63 companies yielding 315 observations. Rising CCC is found to significantly worsen financial distress, while DER exhibits a similar but statistically weak tendency. Firm size fails to moderate either relationship. Substituting Debt to Asset Ratio as an alternative leverage proxy confirms that asset-based leverage significantly deteriorates financial distress, reinforcing the robustness of the main findings.